Aid, peasants and social exclusion - Jean-Louis Arcand; Natascha Wagner (Graduate Institute of International and Development Studies, 2011)
Using unique village census data collected in 2003 and 2008 in Senegal, we assess the impact of a major World Bank-funded Community Driven Development (CDD) program on membership and assortative matching in community-based organizations (CBOs). We implement both standard discrete choice and dyadic regression techniques. We find that channeling development aid through CBOs makes these organizations more inclusive in the sense that a number of tradition-bound assortative matching patterns are partly broken. Ceteris paribus, this leads to more heterogeneous CBOs. On the other hand, the likelihood of CBO membership is reduced in treated villages, with significant differences between men and women. Our results suggest that grassroots level development projects which target CBOs must be carefully designed and executed if they are not to result, paradoxically, in a greater degree of social exclusion, with differentiation by gender playing a crucial role.
Keywords: C21; D71; 330; Community Based Organizations; Dyadic Regression; Gender Differences; Social Exclusion; Entwicklungshilfe; Bürgerbeteiligung; Soziale Integration; Diskrete Entscheidung; Regression; Senegal